Physical Activity And Obesity With Polycystic Ovary Syndrome (Journal of Dhaka Medical College, 2024)
Background: Polycystic ovary syndrome (PCOS) is an emerging endocrine condition that affects women of reproductive age all over the world. Physical activity (PA) is an evidence-based approach in the management of PCOS patients.Methods: This hospital-based case-control study was conducted to find out the association between physical activity and obesity with PCOS among the conveniently selected 172 women.Results: The mean age of PCOS women was 25.0±5.8 years and non-PCOS women was 28.1±7.5 years. The majority of cases (84.9%) were in the 15-30 age groups, in comparison to controls (64.0%). There was a significant association between age and PCOS (p